Do Internal Factors of MSMEs Matter in Islamic Bank Financing Decision? - Naila Najihah; Devi Permatasari (Falah: Jurnal Ekonomi Syariah, 2021)
The existence of an Islamic bank is expected to play a role in increasing and equalizing the economy, including in supporting the growth of MSMEs. Therefore, it is important to know the character of MSMEs in determining Islamic financing. This study aims to examine the effect of the MSME's firm age (calculated from firm incorporation), firm size (as measured by asset ownership) and the level of religiosity of MSME managers in Islamic banks' financing decisions. This study is quantitatif by nature, and the sample of this study comprised 147 MSMEs. Based on the regression analysis, the results found that the firm size is not proven to be influential. Meanwhile, the firm age had a negative effect and the level of religiosity had a significant positive effect on Islamic bank financing decisions. The results of this study contribute to enriching a clear understanding through empirical evidence about how internal factors of MSMEs can influence their behavior in making financing decisions from Islamic bank.